Immature Oocytes from Unprimed Juvenile Mice Become a Valuable Source for Embryo Production When Using C-Type Natriuretic Peptide as Essential Component of Culture Medium. Issue 3 (1st September 2016) - Romero, Sergio; Sánchez, Flor; Lolicato, Francesca; Van Ranst, Heidi; Smitz, Johan
Abstract: C-type natriuretic peptide (CNP) and its receptor natriuretic peptide receptor 2 (NPR2) play a paramount role in the maintenance of oocyte meiotic arrest in antral follicles via the regulation of the intra-oocyte levels of cyclic guanosine monophosphate and cyclic adenosine monophosphate. We investigated the potential of CNP 1) to maintain oocyte meiotic arrest during a prolonged prematuration culture and 2) to sustain acquisition of developmental competence of immature cumulus-oocyte complexes (COCs). Compact COCs were collected from small antral follicles of prepubertal unprimed mice and placed in prematuration culture under different CNP-supplemented media conditions. A preliminary analysis showed a dose-dependent effect of CNP on the maintenance of meiotic arrest. A dose of 25 nM maintained oocytes under meiotic arrest for 24 h, and this period was extended to 48 h in the presence of estradiol. Analysis of transzonal projections of COCs cultured with CNP indicated that oocyte-cumulus connections were well preserved after the prolonged prematuration culture. Furthermore, CNP medium supplemented with FSH and GDF9 promoted oocyte growth and induced a shift in oocyte chromatin configuration from a predominantly dispersed to a condensed configuration. Following in vitro maturation, oocytes cultured under CNP were capable of extruding the first polar body at a high rate (around 80%). Blastocyst formation was significantly improved when oocytes were cultured under CNP-supplemented medium containing FSH and GDF9. This study reports for the first time a prolonged prematuration culture system, with CNP as the pivotal factor, that can efficiently maintain oocytes retrieved from unprimed prepubertal mice under meiotic arrest while promoting their acquisition of developmental competence.